TREATED WASTEWATER USE AND ITS EFFECT ON WATER CONSERVATION, VEGETATIVE YEILD,YIELD COMPONENTS AND WATER USE EFFICIENCY OF SOME VEGETABLE CROPS GROWN UNDER TWO DIFFERENT IRRIGATION SYSTEMS IN WESTERN REGION, SAUDI ARABIA - Balkhair, Khaled S.; El-Nakhlawi, Fathy S.; Ismail, Saleh M.; Al-Solimani, Samir G. (European Scientific Journal, ESJ, 2013)
Irrigation with wastewater is a widespread observable fact in developing countries, especially those exhibiting arid climate conditions. Utilization of large volumes of domestic wastewater effluent is part of an overall integrated water resources management. The objective of this study was to investigate the effect of irrigation by six different treated domestic wastewater qualities on the yield of Cabbage and Lettuce crops under surface and Sub-surface drip irrigation systems. Field experiments were carried out during 2011 and 2012 seasons at the Agriculture Research station of King Abdulaziz University located at Hada Alsham area north east of Jeddah city. The six water qualities were prepared by diluting treated wastewater with local groundwater of the region. The dilution percentages were 0%, 20%, 40%, 60%, 80%, and 100% treated wastewater. Crop water requirement were calculated based of Penman Monteith equation for dry land condition and supplied daily to the crops. The obtained results showed significant impact of wastewater quality and irrigation system and their interactions on vegetative yield and yield components of both crops. Irrigation with 60% and 80% wastewater under sub-surface irrigation system produced the highest yield and yield components in both seasons. Irrigation Water Use Efficiency (IWUE) of cabbage crop increased under the use of subsurface drip irrigation while IWUE of lettuce crop increased under surface drip irrigation system. Among dilution percentages, the 60% gave the highest IWUE in both crops. In conclusion, this study implies an advantage of using treated wastewater in growing vegetable crops. This in turn saves considerable quantities of local groundwater resource.